Injury and illness among athletes during a multi-day elite cycling road race - Yanturali, S.; Canacik, O.; Karsli, E.; Suner, S. (The Physician and Sportsmedicine, 2015)
Objectives: Although road bicycle races have been held for more than a century, injury and illness patterns during multi-day bicycle events have not been widely studied. The aim of this study was to determine the incidence of injury and illness among riders and describe the medical care interventions provided to participants of cycling road races. Methods: A prospective observational study was conducted on the Presidential Cycling Tour of Turkey, which was held between April 26 and May 3, 2015. The race lasted 8 days and covered 1258 km of road. There were 166 elite cycling athletes representing 21 teams from various countries. Data collected pertaining to incidents involving injury or illness included the following: type of injury; anatomical location of injury; details of the medical encounter; location of the intervention; treatment provided; medication administered and disposition of the rider. An injury was defined as a physical complaint or observable damage to the body produced by the transfer of energy of the rider. An illness was defined as a physical complaint or presentation not related to injury. Results: The overall incidence (injury and illness) was 5.83 per 1000 cycling hours. (Injury incidence was 2.82 vs illness incidence of 3.01 per 1000 hours cycling). A total of 31 incidents occurred. Of these, 15 were injuries, while 16 were complaints of a non-traumatic nature. A total of 43 interventions were made in the 15 cases of injury. The most commonly injured body regions were limbs; the majority of injuries involved the skin and soft tissue. The most common medical intervention was wound care (64% of all interventions). Two riders had to withdraw from the race, and one was hospitalized due to a traumatic pneumothorax. None of the non-traumatic cases resulted in withdrawal from the race. Conclusions: A broad spectrum of illness and injury occurs during elite multi-day road races, ranging from simple skin injuries to serious injuries requiring hospital admission. Most injuries and illnesses are minor; however, medical teams must be prepared to treat life-threatening trauma.